Detroit Area Study, 1977: Attitude-Behavior Consistency and Attribution of Responsibility - Schuman, H. ([Verlag nicht ermittelbar], 1984)
The Detroit Area Study is an ongoing series of surveys conducted by the Department of Sociology at the University of Michigan. These surveys serve two purposes: to provide useful survey information about various population characteristics and social issues selected as topics by principal investigators, and to provide actual survey research experience for graduate students. This study explores two topics related to social psychology. Attitude-behavior consistency was measured by asking respondents about their television viewing and their attitudes toward television violence. Follow-up interviews were conducted by telephone to ascertain respondents' actual television viewing. In addition, some respondents were asked to sign a petition regarding violence on television. The study of attribution was conducted by reading respondents a series of vignettes and then asking several questions regarding the characters' responsibility for their actions.